Heretical constructions of anarchist utopianism. Issue 8 (16th November 2020) - Kinna, Ruth
ABSTRACT: This paper examines a relationship between heresy and utopianism forged in nineteenth- and early twentieth-century socialist histories to reveal a significant, pervasive fault-line in the ideological construction of anarchism. It first looks at Marxist narratives which trace the lineages of socialism back to medieval religious dissent and argues that a sympathetic assessment of European heretical movements was qualified by a critique of utopianism, understood as the rejection of materialist 'science'. It then argues that strands of this narrative have been woven into anarchism, looking at three examples: E.V. Zenker's Anarchism (1897), James Joll's The Anarchists (1964/1979) and Saul Newman's From Bakunin to Lacan (2001). The dominant theme is that anarchism promises the transformation of corrupted nature and aims to achieve it though ecstatic violence, cataclysmic revolution and future perfection. Although this Millenarian anarchism is a 'straw man', rather than jettison 'heresy' as an investigative tool, I prefer an alternative conception of heresy derived from Martin Buber's analysis of utopianism in Paths in Utopia (1949) and Michael Bakunin's critique of political theology. I relate utopianism to the rejection of perfection and heresy with faith. By reframing of heresy in this way I seek to correct a long-standing distortion of anarchist ideas.